HUBUNGAN ANTARA BRAND IMAGE DENGAN PENGAMBILAN KEPUTUSAN MEMILIH PRODI PSIKOLOGI UST YOGYAKARTA - Rika Pebriani; Flora Grace Putrianti (Universitas Sarjanawiyata Tamansiswa, 2014)
ABSTRACT The purpose of this study was to determine the relationship between brand image and making the decision of choosing Departement. Subjects in this study were students Departement UST Psychology Yogyakarta. The sampling technique was purposive sampling. The method of analysis used in this study is from Karl Pearson Product Moment.The results of the analysis of decision-making variable data with variable pick Faculty brand image in showing the value of r = 0,619 with significant level p = 0,000 ( p < 0,05). Based on the results of correlation can be stated that there is a significant positive relationship between brand image by selecting the decision-making department of psychology UST Yogyakarta. Correlation test test results showed that the variables of brand image to decision choosing faculty has determinant coefficient of 0,383. Means variable brand image in contributing effectively to decision making choosing Departement by 38,3 %, while the remaining 61,7 % is influenced by other factors such as external factors which consist of prince and promotion or marketing and internal factors consist of motivation to decision making and attitudes towards decision making. Keywords : Brand Image, Decision To Choose Departement.